Peningkatan Pemahaman Nilai-Nilai Anti Korupsi Guru Dan Siswa Di Lingkungan Sekolah Sman 1 Kota Serang Provinsi Banten - Furqon, Eki; Rayhan, Ahmad; Vitrana, Mokhamad Gisa; Muslih, Muhamad (Universitas Negeri Gorontalo, 2023)
Instilling anti-corruption values is something that must be done from children to adults, and is done anywhere, even in schools or learning places, especially for high school students in Serang City. These Anti-Corruption Values must be taught and practiced in schools so that they can be brought and practiced to society by students, so that opportunities for committing Corruption in everyday life can be minimized. Teachers as educators also have an important role in directing students not to commit corruption, no matter how small, in real life. The instillation of Anti-Corruption Values is in accordance with the 9 Integrity Values issued by the Corruption Eradication Commission which are believed to be able to prevent criminal acts of corruption, namely including the values of